2009
DOI: 10.1002/elps.200800436
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the interaction of cefadroxil with different metal ions using CE

Abstract: The present study describes the application of CE to investigate the interaction between a cephalosporin, cefadroxil and different metal ions. This study aims at quantifying the interaction of cefadroxil with Zn(2+), Al(3+), Fe(3+), Cu(2+) and Co(2+) ions using the effective electrophoretic mobility as a parameter for calculation of the reaction association constant (K). For this purpose, the electrophoretic mobilities of cefadroxil at different metal ion concentrations in citrate buffer pH 3.6 were determined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 14 publications
(18 reference statements)
0
5
0
Order By: Relevance
“…Recently, CE once more proved advantageous as a rapid and simple screening method [48], which provides quantitative results of the interactions of drugs with metal ions. For high throughput screenings of several drugs with one protein, the present work suggests a reduced experimental design in which single experiment could suffice, later repeating the experiments for substances with interesting binding properties.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, CE once more proved advantageous as a rapid and simple screening method [48], which provides quantitative results of the interactions of drugs with metal ions. For high throughput screenings of several drugs with one protein, the present work suggests a reduced experimental design in which single experiment could suffice, later repeating the experiments for substances with interesting binding properties.…”
Section: Resultsmentioning
confidence: 99%
“…We could not investigate the effect of Cu 2+ ions on the flux of cefadroxil due to the instability of its solution with cefadroxil at 37 °C. In a previous study [3] we determined the association constant of the interaction of cefadroxil with zinc and with aluminium ions. Our results indicated that the reaction strength between cefadroxil and metals used follows the order: Zn 2+ > Al 3+ with association constants of 1546.52 and 451.57 L/mmol respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The details of preparation and characterisation of cefadroxil-metal complexes were mentioned in our previously published paper [3]. The Caco-2 human colon carcinoma cell line was routinely cultured with minimum essential medium supplemented with 10% fetal bovine serum, 1% nonessential amino acid solution, and gentamicin (45 µg/mL) [9].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several analytical methods such as high performance liquid chromatography (HPLC) [7,11,12], liquid chromatography mass spectrometry (LC-MS) [13], electro chromatography [14,15], capillary zone electrophoresis [16][17][18][19], chemiluminescence [20][21][22], spectrophotometry [23][24][25] and electroanalytical techniques [26,27] were reported in the literature for the quantification and detection of the CFDL. Among them, spectrophotometry and electrochemical methods are preferable because ease of use, ecofriendly, and costeffective techniques for routine analysis of CFDL in complex matrices.…”
Section: Introductionmentioning
confidence: 99%